Alkaline Hydrolysis of Organophosphorus Pesticides: The Dependence of the Reaction Mechanism on the Incoming Group Conformation - Dyguda-Kazimierowicz, Edyta; Roszak, Szczepan; Sokalski, W. Andrzej (The journal of physical chemistry. B, 2014)
The fundamental mechanism of organophosphate hydrolysis is the subject of a growing interest resulting from the need for safe disposal of phosphoroorganic pesticides. Herein, we present a detailed ab initio study of the gas-phase mechanisms of alkaline hydrolysis of P–O and P–S bonds in a number of organophosphorus pesticides, including paraoxon, methyl parathion, fenitrothion, demeton-S, acephate, phosalone, azinophos-ethyl, and malathion. Our main finding is that the incoming group conformation influences the mechanism of decomposition of organophosphate and organothiophosphate compounds. Depending on the orientation of the attacking nucleophile, hydrolysis reaction might follow either a multistep pathway characterized by the presence of a pentavalent intermediate or a one-step mechanism proceeding through a single transition state. Despite a widely accepted view of the phosphotriester P–O bonds being decomposed exclusively via a direct-displacement mechanism, the occurrence of alternative, qualitatively distinct reaction pathways was confirmed for alkaline hydrolysis of both P–O and P–S bonds. As the pesticides included in our quantum chemical analysis involve organophosphate, phosphorothioate, and phosphorodithioate compounds, the influence of oxygen to sulfur substitution on the structural and energetic characteristics of the hydrolysis pathway is also discussed.